High-mast lighting as an adequate way of lighting pedestrian paths in informal settlements?. (2020) - Kretzer, David Michael
Abstract: Lighting of pedestrian paths fulfils crucial needs for informal settlement dwellers. A common technological approach in some countries to address these needs is to provide high-mast luminaires. In this paper it is shown by computer simulation that those luminaires are not able to create adequate consistent lighting conditions in common forms of informal settlements. Illuminance uniformity requirements are not met within the entire pedestrian path network. Furthermore, a significant part of the light is emitted on the dwellings' roof and hence results in light pollution.